The politics of the selective gaze: closed Circuit Television and the policing of public space - Williams, Katherine S. (Crime, law and social change, 2000)
This paper gives first an explanation for the rapid development of Closed Circuit Television (CCTV) throughout Britain. This considers the implications of its rapid proliferation on the geographies of public space and highlights the selectivity of the gaze of the surveillance cameras and the consequent potential for the exclusion of certain groups from public space. The paper then extends this by using research from two rural towns to address three basic questions: how the cameras are used for direct law enforcement; how this use is governed; and how the public react to the use of CCTV. It concludes that by stressing the selectivity of the surveillance and drawing the implications of this for enforcement and governance, and also stressing the extent to which the placing and timing of the use of the cameras fails to reflect the revealed preferences of the communities involved.